2021
DOI: 10.18543/tjhe-9(1)-2021pp127-155
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the university competitiveness in the Czech Republic

Abstract: The number of students at Czech universities had been growing continuously until 2010. In 2010, almost 400,000 students studied there. Since then, this number has declined every year. Pressure on present-day universities has been accruing due to the competitive environment. The only way to strengthen competitiveness is to improve constantly the quality and image. The objective of this paper is to verify what factors are important for students regarding their satisfaction and what factors could be key for suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The competitiveness of educational institutions has constantly been growing according to this factor, which in turn, leads to missed gaps in both the educational environment and the labor market (Chládková et al, 2021). According to the online survey, the study identified the problems in the successful implementation of SUMS in modern realities.…”
Section: Discussionmentioning
confidence: 99%
“…The competitiveness of educational institutions has constantly been growing according to this factor, which in turn, leads to missed gaps in both the educational environment and the labor market (Chládková et al, 2021). According to the online survey, the study identified the problems in the successful implementation of SUMS in modern realities.…”
Section: Discussionmentioning
confidence: 99%
“…The top seven public universities from the Czech Republic according to the evaluation by The times higher education (n.d.) were included (Chládková et al, 2021) in the research sample. Their size ranges from 9 to almost 50 thousand students.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Pressure on present-day universities has been accruing due to the competitive environment". 24 In 2020, Czech HEIs enrolled 43,001 domestic and 2,730 international students, 29,534 Czechs and 571 foreigners graduating, respectively. 25 The numbers of admitted students and those of graduates differ considerably; there are several times more international applicants than graduates.…”
Section: Theoretical Backgroundmentioning
confidence: 99%